(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Insecticides are widely used in agriculture all over the globe for stopping growth of unnecessary weeds and insects on the plants and crops, Chloryrifos is one among these. Chlorpyrifos, an organophosphorus chemical, was initially introduced and patented by Dow Chemical Company in 1965, and it is currently marketed commercially as “Dursban” for indoor use and “Lorsban” for crop protection. Insecticides when taken continuously causes toxicity in the body leading to serious problems and fatality. There are many methods which focus on the detection and identification of such poisoning in the samples. The purpose of this study was to develop a more accurate way of identifying chlorpyrifos insecticide in urine and viscera samples. Chlorpyrifos inhibits acetylcholinesterase in both the neural synapse and the plasma. The method’s selectivity was acceptable in all blank samples, with a negligible matrix effect. To assess % recovery, three repeats were performed at various doses. In biological matrices, chlorpyrifos insecticide was shown to have a 92.4 percent recovery rate. The limit of detection